A rare complication of accidental dural puncture during epidural insertion for labour analgesia. Issue 1 (8th April 2019) - Shields, N.; Innes, E.; Goodman, J.
Summary: A 33‐year‐old multiparous term parturient requested an epidural for labour analgesia. An accidental dural puncture was noted at the time of epidural needle insertion and an intrathecal catheter was placed. The intrathecal catheter was removed 10 h later and was noted to be intact. The following day, there was a significant leak of clear fluid from the catheter insertion site. Cerebrospinal fluid was detected using beta‐trace protein testing. The patient remained asymptomatic and we deduced the cause could be a cutaneous fistula. Similar published reports have suggested the causes of similar presentations could include leakage of interstitial oedema, local anaesthetic or cerebrospinal fluid. It is important to consider the diagnosis of clear fluid leakage following an accidental dural puncture and the management of a cerebrospinal fluid‐cutaneous fistula in the absence of neurological symptoms.